Numerical investigation of particle trapping in various groove configurations in straight and bent flow channels. (August 2020) - Florio, LA
A novel computational technique is applied to investigate particle trapping in straight and bent channel flow paths with various groove configurations in high-speed compressible, particle laden flow. The technique is valid for particle sizes of the same order of magnitude as the groove dimensions and where the particle–flow path, particle–particle, and particle–flow interactions play significant roles in determining the particle motion. The sacrificial grooves within the flow path can remove particles from the flow to reduce particle impact-induced wear. The feasibility of the trapping grooves and the conditions for which they are most beneficial can be gleaned from analysis of the model results. Three groove configurations are studied: a straight groove, a flared groove, and a 45 degree angle groove, for the same groove entrance size, groove depth, and spacing in a straight channel and a channel with a 90 degree bend. A transient maximum of 22% of the particles were trapped for the flared groove for the bent channel and a transient maximum of 15% of the particles for the straight channel configuration. The second groove of the bent channel produces the greatest single groove particle holding of 8.25% of all of the particles for the flared grove configuration. The contributions of the groove positioning, groove shape, gas flow, and particle interaction conditions to the trapping characteristics can be readily obtained from examination of the model results since the modeling technique includes detailed treatment of particle–flow path and flow interactions, allowing for the study of the mechanisms acting to trap the particles within the grooves.